2014
DOI: 10.1021/pr4012848
|View full text |Cite
|
Sign up to set email alerts
|

Important Role of SUMOylation of Spliceosome Factors in Prostate Cancer Cells

Abstract: Sentrin/SUMO (small ubiquitin-like modifier)-specific proteases (SENPs) have been implicated in the development of prostate cancer. However, due to the low abundance of SUMO-modified proteins and high activity of SENPs, the SUMO substrates affected by SENPs in prostate cancer cells are largely unknown. Here, we identified SI2, a novel cell-permeable SENP-specific inhibitor, by high-throughput screening. Using SI2 as a way of inhibiting the activity of SENPs and the SUMO stably transfected PC3 cells as a prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…A sumosylated USP39 has been shown to promote the proliferation of PC-3 and LNcap cells [17]. Nevertheless, the clinical significance of how USP39 is related to PCa has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sumosylated USP39 has been shown to promote the proliferation of PC-3 and LNcap cells [17]. Nevertheless, the clinical significance of how USP39 is related to PCa has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [16] have reported that USP39is overexpressed in breast cancer, and is involved in the tumorigenesis. Wen et al [17] have reported that USP39 is a target of SUMOylation specific protein (SENP) in the proliferation of PCa cells. However, the clinical relevance of USP39 in PCa and its molecular mechanism have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, large-scale experiments and computer predictions suggest that sumoylation [87,88], neddylation [88,89] and ubiquitination [90,91,92,93,94] can occur, and that there may be several kinase target sequences.…”
Section: Synthesis and Fate Of Oat—from Gene To Proteinmentioning
confidence: 99%
“…For example, the specific acetylation activity pattern of SUMO was shown to alter protein phosphorylation patterns, thus affecting the activity of certain regulatory proteins (35). It has been hypothesized that SENPs modulate the cell cycle and tumorigenesis, utilizing divergent mechanisms (3638). In the present study, SUMO modification of mRNA expression levels in CAL27 cells differed according to the VPA concentration.…”
Section: Discussionmentioning
confidence: 99%